Strategic Protocol in Crisis: A Conceptual Framework for Government Public Relations in State-Owned Energy Enterprises - Susetyo, Asti Sih; Pradana, Galang Yoga; Wahyuni, Kholifah; Subrata, Pramudya Ibnu (CITACONOMIA, 2026)
This conceptual article explores the operational paradox of PT Pertamina (Persero) as a National Oil Company (NOC) caught between its commercial mandates and the rigid bureaucratic protocols of the state. While protocol is traditionally viewed as a static administrative function, this study identifies it as a significant structural barrier—termed